Representasi Multikultural dalam Pertunjukkan Musik Dangdut Koplo - Kamaluddin, Muhammad (Prosiding University Research Colloquium, 2018)
This research describes the matters of multicultural representation in dangdut koplo. Multicultural colors are symbolically represented by songs sung by their singers. The songs are sung with the rhythm of musical instruments that accompany the show. The description of the symbolic representation is done by entering some song data into the semiotic analysis model. From the multiple analysis of semiotic analysis, the idea of cultural semiotics is the main reference. The research methodology used is descriptive qualitative tradition approach. This is done to get the data in the form of song lyrics in dangdut koplo show with the method refer to note. Data is obtained from online impressions of youtube.com pages. From here it is known that the elements of multicultural enter in arbitrary into musical performances dangdut koplo. Of the existing, cultural diversity in this genre of music is represented by songs that speak Javanese, Sundanese, Indonesian, Arabic, Indian, English, and even Latin as a symbol.